(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: About 2% of all malignant tumours occur in infancy and childhood. Malignancy is the second common cause of childhood death in developed world, accounting for 10 - 12.3% of all childhood deaths. Eighty eight percent of worlds children live in developing countries, where access to adequate care is limited. Incidence of childhood cancer is increasing in this region gradually. Objectives: The objective of this study was to find out the histomorphological pattern of childhood cancers in our country and assess the trends of malignancies in different age group. Methods: This prospective study was carried out from January 2008 to January 2012. During this period data was analyzed for the malignancies occurring in the age group 0-14 years. Data was categorized according to incidence of paediatric malignancies in different age groups, sex and types of tumours. All the children below 15 years with confirmed diagnosis of cancer by means of histopathological examinations were included in this study. Results: Total 3120 patients were diagnosed as having malignancies at Armed Forces Institute of Pathology (AFIP), Delta Hospital Ltd & Bangabandhu Sheikh Mujib Medical University (BSMMU) Dhaka, out of which 60 cases were paediatric malignant tumours. Overall incidence of paediatric tumour was 1.92%. Out of which 26 cases (43.33%) were female and 34 (56.66%) cases male. The male - female ratio was 1.3:1. Males were more affected than females. The peak incidence of paediatric tumors (37%) was found in children between the age group 10 to 14 yrs. The pattern of childhood tumours shows wide variation among the age groups. In this study, at 0-4 yrs age group small round cell tumours (Neuroblastoma, Retinoblastoma), 5-9 yrs germ cell tumour, 10-14 yrs bone tumour (Ewing sarcoma, Osteosarcoma) were the commonest tumour. Conclusion: We conclude that there are certain notable differences between tumours of our study and those reported from other parts of the world. In our study small round cell tumor is most frequent childhood tumour. DOI: http://dx.doi.org/10.3329/jafmc.v9i1.18727 Journal of Armed Forces Medical College Bangladesh Vol.9(1) 2013: 57-62